Colitis-targeted hybrid nanoparticles-in-microparticles system for the treatment of ulcerative colitis. (15th October 2020) - Naeem, Muhammad; Lee, Juho; Oshi, Murtada A.; Cao, Jiafu; Hlaing, Shwe Phyu; Im, Eunok; Jung, Yunjin; Yoo, Jin-Wook
Abstract: Nanoparticle (NP)-based drug delivery systems accumulate in the disrupted epithelium of inflamed colon tissue in ulcerative colitis. However, premature early drug release and uptake or degradation of NPs during their passage through the harsh gastric or intestinal environment compromise their therapeutic outcomes. This study aimed to develop an advanced colitis-targeted hybrid nanoparticles-in-microparticles (NPsinMPs) drug delivery system to overcome the aforementioned challenges. First, sustained drug releasing poly(lactic-co-glycolic acid) NPs were generated and further encapsulated in pH-sensitive Eudragit FS30D MPs to ensure complete drug protection in a gastric-like pH and for selective delivery of NPs to the colon. SEM and confocal microscopy for the NPsinMPs revealed successful NP encapsulation. NPsinMPs prevented drug release in an acidic gastric-like and intestinal-like pH and presented a sustained release thereafter at an ileal and colonic pH, indicating the degradation of the outer pH-sensitive MPs and release of NPs. Furthermore, in vivo imaging of gastrointestinal tract of a colitis mouse orally administered with fluorescent NPsinMPs revealed higher fluorescence intensities selectively in the colon, demonstrating the release of loaded NPs and their concomitant accumulation at the site of colon inflammation. NPsinMPs markedly mitigated experimental colitis in mice indicated by improved histopathological analysis, decreased myeloperoxidase activity, neutrophils and macrophage infiltration, and expression of proinflammatory cytokines in colonic tissues compared with NP-treated mice. The present results show the successful formulation of an NPsinMP-based drug delivery system and provide a platform to improve NP-based colon-targeted drug delivery through improved protection of encapsulated NPs and their payload in the early small intestine. Graphical abstract: Image, graphical abstract